(untitled) (Al-Academy, 2025)
The semantic levels in the theatrical performance vary according to the diversity of its references. These references formed the link between the message and its recipient. Interpretations of the offer differ depending on the references between the two parties. This research charts its path in four chapters. The first (methodological) chapter deals with (the research problem), which was determined by the diversity of semantic levels, which led to the clash of those meanings and the implications that resulted from them. The (importance of the research) is that it studies the phenomenon of multiple levels of significance in building the image, and (the goal of the research) is to reveal the semantic levels of the theatrical image. The second chapter (theoretical framework) includes two sections: the first: (transformations of the sign between text and presentation), while the second: (references that form the image). The third chapter (research procedures) contained the research community, research tools, and the research sample, which was represented by the performance of the play (Silk). Chapter Four (Results and Conclusions) Among the most important results: (The diversity of visual formations formed a semantic level that contributed to achieving reduction and condensing meaning to reveal the essential contents). As for the most important conclusions: (The theatrical performance did not benefit from the characteristics of the sign represented by (transformation and semantic generation).